EVALUATION OF SOME DISINFECTANTS ON TOTAL MICROBIAL LOAD IN TEATS CUPS - Arif Kassim AL-Hubaety; Ashna Khursheed Darweesh; Aseel Daoud Najem (Mesopotamia Journal of Agriculture)
This study was conducted at the farm of Animal Production ,College of Agriculture and Forestry- University of Mosul, to study the effect of using a number of disinfectants on Total Viable Bacterial Count (TBC) and Total Fungi (TF) on  teat cups which they are a part of the automatic milking machine.The following disinfectants were used with two concentration (5 and 10%) of Dettol; Chloroxylenol and Hydrogen Peroxide. Water was also used at temperature at (700C).Teat cups were immersed in  a bowl containing each of the above mentioned disinfectants for one minute. The results revealed that in control treatment( without using any disinfectants) the (TBC)  was 8X105 (CFU) and there was a reduction in the (TBC) after the use of the above mentioned disinfectants at 5%, and water (700C ) they were  33X103 ; 35 X 103; 25X103; 37 X103 (CFU) respectively. One log reduction in the (TBC) was reported after increasing the concentration of these disinfectants to 10% and they were 15X102; 30X102, 15X102 and 37 X102 (CFU) respectively. For the (TF) in teat cups there was a reduction (TF)  from 4.3X105 in the control treatment to 5X102; 7X102  and 6X102 (CFU)  after using the above disinfectants at aconcentration 5% respectively, but when disinfectant concentration were increased to10%, there was one log reduction in (TF) to 4X101; 6X101; and 3X101 (CFU)  respectively. It could be concluded, from this study, that the best disinfectant was hydrogen peroxide in both concentration.